KEMITRAAN MASYARAKAT DALAM PROGRAM KELUARGA BERENCANA DENGAN METODE KONTRASEPSI JANGKA PANJANG DI DI KELURAHAN BANDAR LOR KEDIRI - Shinta Kristianti; Triatmi Andri Yanuarini; Ratih Novitasari (Politeknik Kesehatan Kemenkes malang, 2021)
Indonesia is still facing the real threat of the increase in population. As the 4 country with the largest population in the world, Indonesia must be able to control the high birth rate. Long-Term Contraceptive Method (LTCM) is one solution of the birth control program that can be implemented, however the number of reproductive women who became Family Planning Program acceptors has not reached the expected target. The aim of this activity is empowering volunteers to increase the scope of LTCM acceptors on reproductive women in Bandarlor Kediri. This activity is held from August to September 2021. The first activity was held at Bandarlor Hall where the volunteers were given refreshing about the role of Family Planning Program volunteers in contraceptive services and socialization of “Pandu Kader KB” book. In addition, the volunteers are given motivation to invite reproductive women who haven’t use LTCM. The second activity was held at Sukorame Public Health Center to provide IUD and implant services. Evaluations of questionnaires filled out about volunteers knowledge in volunteer roles and duty increased from 57% to 77%, and volunteers knowledge of LTCM increased from 30% to 60%. For the number of the new LTCM acceptors, there is an addition of 20 people. The follow-up plan have increase the construction of Family Planning Program acceptors in a continuous and comprehensive manner so that they are more educated and motivated to carry out their duties in increasing the number of LTCM acceptors in their region.